1999
DOI: 10.1063/1.124032
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of rare-earth manganite-oxide thin films by metalorganic aerosol deposition technique

Abstract: A chemical deposition technique based on the use of solutions of metal-chelate coordination compounds has been applied to prepare rare-earth–manganite-oxide thin films. La0.67Ca0.33MnO3 and La0.67Sr0.33MnO3 thin films have been grown epitaxially on MgO(100) substrates and characterized by structural (x-ray diffraction analysis, atomic force microscopy) and magnetotransport (T=4.2–300 K, and B=0–5 T) measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 21 publications
1
61
0
2
Order By: Relevance
“…The lowest roughness achieved by an ablation technique was performed by PLD and found to be about 0.2 nm on about 10 nm thick films [24]. Similar results were featured by Metalorganic Aerosol Deposition (MAD) [25,26], but in that case the 0.2 nm roughness is claimed for thicker films of 80 nm. Best MBE roughness reached as low as 0.4 nm [27] and was found for 9 nm films.…”
Section: Introductionsupporting
confidence: 64%
“…The lowest roughness achieved by an ablation technique was performed by PLD and found to be about 0.2 nm on about 10 nm thick films [24]. Similar results were featured by Metalorganic Aerosol Deposition (MAD) [25,26], but in that case the 0.2 nm roughness is claimed for thicker films of 80 nm. Best MBE roughness reached as low as 0.4 nm [27] and was found for 9 nm films.…”
Section: Introductionsupporting
confidence: 64%
“…At this point, it is also important to mention that the optical properties study was performed comparing bulk material and films in overdoped region for x > 0.5, with the additional motivation to clarify the role of disorder in the physics of overdoped La 1−x Ca x MnO 3 manganites [23]. The films in this study were prepared in the same way as the films in our study [24]. The results confirmed that disorder effects are more pronounced in bulk material than in films as well as that disorder must be taken into account when analyzing low-energy properties.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, results from a 200 nm thick La 0.7 Ca 0.3 MnO 3 (LCMO) film which was deposited by a metalorganic aerosol deposition (MAD) method [20] are presented. MgO substrates were used in order to get epitaxial growth of the films [21].…”
mentioning
confidence: 99%